The Physiological Need of The Body For Nutrients And The Importance Of Rational Nutrition (Open Herald: Periodical of Methodical Research, 2024)
Food ration is the composition and quantity of food products, which must be included in the daily food ration. The following hygienic requirements are imposed on the daily food ration, which ensures that the diet is reasonable. The energy value of the food ration is the maintenance of the nutrients included in the food in accordance with the physiological needs of the body. The body's physiological need for nutrients depends on each person's gender, age, body structure, type of work, climatic conditions, and the physiological state of the body (for women, the physiological state is monthly menstruation).